Edukasi Dan Aksi Bersih Pantai: Meningkatkan Kesadaran Masyarakat Pesisir Terhadap Kebersihan Laut - Fatoni, Fatoni; Alimsyah, Andi Saiful; Alim, Bahrul; Raswadi, Mohammad Dika; Butsiarah, Butsiarah (Journal Of Human And Education (JAHE), 2025)
Abstract The problem of waste in coastal areas is increasing due to low public awareness of the cleanliness of the marine environment. Waste that accumulates on beaches and coastal waters not only pollutes the ecosystem, but also threatens the lives of marine biota and the welfare of communities that depend on the fisheries and tourism sectors. This community service activity aims to increase awareness and participation of coastal communities in maintaining environmental cleanliness through the "Education and Beach Clean Action Program”. The methods used in this program include socialization regarding the impacts of marine pollution, community-based waste management training, and beach clean actions involving local communities, students, and related stakeholders. Educational activities are provided in the form of interactive lectures, group discussions, and demonstrations of environmentally friendly waste management practices. Meanwhile, beach clean actions are carried out directly with waste sorting techniques to increase public awareness of the importance of reducing plastic waste. The results of this activity show an increase in public understanding of the impacts of marine pollution and an increase in active involvement in maintaining beach cleanliness. In addition, this program has also succeeded in building a network of cooperation between the community, local government, and environmental organizations in efforts to preserve coastal ecosystems. With education and real action, coastal communities' awareness of marine environmental cleanliness can continue to increase, thereby creating a healthier and more sustainable environment. Keywords: education, clean beaches, public awareness, marine cleanliness